Negative effect of zinc compounds on hydration kinetics of ordinary Portland cement. Issue 1 (January 2021) - Matejka, L; Siler, P; Novotny, R; Svec, J; Masilko, J; Soukal, F
Abstract: Metals and metal containing compounds have significant effect on cement hydration mechanism and kinetics. The recycling of waste materials leads to increase of content of metals in various industrial products and visibly affects properties of the Portland cement. One of the metals that has been known to drastically increase the setting time is zinc. Zinc forms various hydroxyl species with calcium cations. Pore solution thus has lowered concentration of calcium which suppresses formation of portlandite. Due to insufficient concentration of calcium the formation of CSH gel and further hydration of clinker grains is inhibited The aim of this study is to quantify the negative effects of zinc at different concentrations at ambient temperature at 20°C. Isoperibolic calorimetry was used to measure the negative effects of zinc on hydration kinetics of ordinary Portland cement. Zinc was added to the cement in the form of two soluble salts Zn(NO3 )2 hydrate, ZnCl2 and a poorly soluble compound ZnO. The concentration of zinc added was chosen between 0.1 and 1 wt. % of clinker. Significant retardation of cement hydration with increasing zinc content was proven.